Complex immune network and regional consistency in the human gastric mucosa revealed by high-resolution spectral cytometry - Ángel De Prado; Paloma Cal-Sabater; Aida Fiz-López; Sandra Izquierdo; Daniel Corrales; Francisco Pérez-Cózar; Juan H-Vázquez; Elisa Arribas-Rodríguez; Cándido Perez-Segurado; Álvaro Martín Muñoz; José A. Garrote; Eduardo Arranz; et al. (Scientific Reports)
Abstract The immune cellular landscape from the gastric mucosa remains largely unknown despite its relevance in several inflammatory conditions. Human gastric biopsies were obtained from the antrum, body and incisura from 10 individuals to obtain lamina propria mononuclear cells that were further characterized by spectral cytometry. Phenotypic hierarchical analyses identified a total of 52 different immune cell subsets within the human gastric mucosa revealing that T-cells (> 60%) and NK cells (> 20%) were the main populations. Within T-cells, CD4+ and CD8+ were equally represented with both subsets displaying mainly a memory and effector phenotype. NK cells, on the contrary, were largely of the early phenotype. No regional differences were observed for any subsets among the 3 locations. Following unsupervised analysis, a total of 82 clusters were found. Again, no differences were observed amongst locations although a great degree of inter-individual variability was found, largely influenced by the presence of H. pylori infection and dyspepsia. We have unraveled the human gastric immune cellular subset composition and a unique interindividual immune fingerprint with no inter-regional variations.